An ethnography of the Parsees of India 1886-1936 - Shah, Arvindbhai M. 1931-2020; Lobo, Lancy 1948- (Routledge, 2022)
"This volume explores Parsee culture and society derived through essays from the Journal of Anthropological Society of Bombay (1886 - 1936). Through essays by Jivanji Jamshedji Modi, Bomanjee Byramjee Patell, Rustamji Munshi, eminent Parsee scholars, it discusses the social and cultural frameworks in the Parsee life nearly a 100 years ago."